2015
DOI: 10.1155/2015/472605
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Tumor in a 31-Year-Old Female with a Facial Port-Wine Stain

Abstract: Pyogenic granuloma is a type of inflammatory hyperplasia often seen in the oral cavity and occurs in response to stimuli such as local irritants and hormonal factors. Pyogenic granulomas associated with pregnancy are referred to as pregnancy tumors. This report describes the presentation and surgical management of a large pregnancy tumor occurring in a patient with an overlying isolated facial port-wine stain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to the literature, 5,11 female sex hormones supplement the expression of angiogenic factors such as basic fibroblast growth factor and vascular endothelial growth factor along with declining the expression of tissue necrosis factor-alpha which in turn causes diminished cell apoptosis. 12 Thus, pregnant women exhibiting the incidence of pyogenic granulomas commonly establishes significantly increased basic fibroblast growth factor, supplementary vascular endothelial growth factor, and fewer tumor necrosis factor-alpha. 12 Besides, certain medications like indinavir (Crixivan), isotretinoin (Accutane), acitretin (Soriatane), and birth control pills can cause this overgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, 5,11 female sex hormones supplement the expression of angiogenic factors such as basic fibroblast growth factor and vascular endothelial growth factor along with declining the expression of tissue necrosis factor-alpha which in turn causes diminished cell apoptosis. 12 Thus, pregnant women exhibiting the incidence of pyogenic granulomas commonly establishes significantly increased basic fibroblast growth factor, supplementary vascular endothelial growth factor, and fewer tumor necrosis factor-alpha. 12 Besides, certain medications like indinavir (Crixivan), isotretinoin (Accutane), acitretin (Soriatane), and birth control pills can cause this overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, pregnant women exhibiting the incidence of pyogenic granulomas commonly establishes significantly increased basic fibroblast growth factor, supplementary vascular endothelial growth factor, and fewer tumor necrosis factor-alpha. 12 Besides, certain medications like indinavir (Crixivan), isotretinoin (Accutane), acitretin (Soriatane), and birth control pills can cause this overgrowth. 13 Systemic and topical retinoids, antiretrovirals, antineoplastics, and antineoplastics are also responsible for their manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…They commonly tend to appear after first trimester, grow swiftly, and classically regress after parturition. 9 Various authors demonstrated that 55% of overgrowths involved the maxilla, and 83% arose in the gingiva. 10 Various etiological factors that trigger the periodontal inflammation can be chronic irritation, hormonal factors and various drugs.…”
Section: Introductionmentioning
confidence: 99%